3D cytotoxic and histon deacetylase (HDAC) inhibitory activities of triterpenoids isolated from leaves of Viburnum sambucinum - Tra, Nguyen Thanh; Thu Ha, Nguyen Thi; Cham, Ba Thi; Tu Anh, Le Thi; Thao, Do Thi; Nga, Nguyen Thi; Mai Huong, Doan Thi; Cuong, Pham Van (Vietnam Journal of Chemistry, 2017)
The plant Viburnum sambucinum has been known under the local name “Vót dạng cơm cháy” belongs to Viburnum genus, a member of the Caprifoliaceae family. Many plants of Viburnum genus are well known for their medicinal properties and are used in the folk medicine for the treatment of various diseases. A variety of structures have been reported from the plants of the genus, such as diterpenes, triterpenes, iridoids, sesquiterpenes, flavonoids, etc. In this study, we describe 3D cytotoxic and histone deacetylase (HDAC) inhibitory activities of two nordammarane triterpenoids hupehenol D (1) and 12β-hydoxy-3,15-dioxo-20,21,22-23,24,25,26,27-octanordammanrane (2) isolated from the leaves of Viburnum sambucinum. The result showed that (1) and (2) exhibited a strong activity against 3D models of LLC cell line with the IC50 value ​​of 25.89 µM and 15.58 µM, respectively. Compound 1 weakly inhibited activity of enzyme HDAC with the IC50 of 20.78±2.86 mM while compound 2 exhibited no effect on HDAC at 25 mM. Keywords. Viburnum sambucinum, Caprifoliaceae, hupehenol D (1), 12β-hydoxy-3,15-dioxo-20,21,22-23,24,25,26,27-octanordammanrane (2), 3D cytotoxic, HDAC inhibitory activity.